The Impact of Job Separation Experience on Job Search Duration - Mery Permata Defi; Dwini Handayani (UNIVED Press, 2026)
This study aims to analyze the impact of job separation experiences, both voluntary and involuntary, on job search duration in Indonesia. Utilizing data from the 2023 National Labor Force Survey (Sakernas), the research employs an Ordinary Least Squares (OLS) regression model with various control variables, including age, gender, marital status, household head status, household size, education level, training, and residential location. The analysis reveals that individuals who experience voluntary separation take longer to find new employment compared to those with involuntary separation. This study offers a novel approach by distinguishing between these two categories of job separation while exploring their interaction with individual characteristics. The findings are expected to provide empirical support for adaptive labor policies aimed at accelerating workforce transitions into stable and decent employment in Indonesia.